Spatial Variation in Bird Community Composition in Relation to Topographic Gradient and Forest Heterogeneity in a Central Amazonian Rainforest. (30th October 2011) - Cintra, Renato; Naka, Luciano N.
Abstract : We investigated the effects of landscape features and forest structure on the avian community at the Reserva Florestal Adolpho Ducke near Manaus, in the Brazilian Amazon. We sampled the landscape and forest in 72 50 × 50 m plots systematically distributed in the reserve, covering an area of 6, 400 ha. The avifauna was sampled using mist nets and acoustic surveys near the plots. We found no significant relationships between landscape features and forest components in the plots and the number of bird species and individuals sampled. Results of Principal Coordinate Analyses, however, showed that bird species composition changes along a topographic gradient (plateau-slope-valley), and also in relation to leaf litter depth and distance to forest streams. We also found compositional differences in the avian community on the eastern and western water basins that compose the reserve. Our results suggest that although most bird species occur throughout the reserve, many species track differences in the landscape and the forest structure.